HUBUNGAN FAKTOR RISIKO LINGKUNGAN TERHADAP KEJADIAN PENYAKIT PNEUMONIA BALITA DENGAN PENDEKATAN ANALISIS SPASIAL DI KECAMATAN SEMARANG UTARA - Fauziah El Syani; Budiyono Budiyono; Mursid Raharjo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Trend of cases pneumonia in children under five years in the sub-district of North Semarang was increased from 2011 to 2013. Sub-district of North Semarang had bad environmental conditions, high density, and highly susceptible to infectious diseases. Based on those cases, there was no clear information how those cases spread related to environmental risk factors. This research aimed to do spatial analysis pneumonia in children under five years associated with type of fuel, temperature, humidity, residential density, population density, density homes, education level, and income level with analysis unit by 28 RW in Bandarharjo and Tanjung Mas. This study was an observational study with cross sectional design using Geographic Information System (GIS). The research sample of 98 respondents was used proportional random sampling method. Primary data was collected using questionnaires, observation sheets, and the measurement point of coordinate using GPS. The collected data would be analyzed with univariate, bivariate and spatial analysis. Results of univariate were 97 respondents with risk types of fuel, 89 houses at risk of temperature, 61 houses of humidity risk, 45 houses with high-density residential, 24 RW with high population density, 18 RW with high-density homes, 47 respondents with low maternal education level, and 36 respondents with low income levels. Statistical analysis showed that there was an association between humidity (p<0,001), residential density (p=0,005), population density (p= 0.038), and income level (p = 0,003) with the incidence of pneumonia in children under five years. The conclusion was the analysis of spatial distribution pattern incidence of pneumonia in the village of Bandarharjo and Tanjung Mas showed clustered patterns. The predominant distribution pattern of environmental risk factors pneumonia were population density, humidity, and level of income.